2021
DOI: 10.3390/su132313489
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Succession Management on Small and Medium Enterprises’ Sustainability in Lagos State, Nigeria

Abstract: This study investigated the impact of succession management on small and medium enterprises’ (SMEs’) sustainability in Lagos, Nigeria. The study adopted a descriptive survey research method and its participants were selected from five SMEs across Lagos State, based on their number of years of operating, staff strength, and branch locations. The enterprises included Gnakk Enterprises, Dreamville School, Vitus Cosmetics, Osi Ventures, and Chijioke Frozen Foods. The Pearson product moment correlation coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Workplace performance has been the core of all organizational activities. Moreover, it is the position of Monyei et al [3] and Yasar et al [38] that workplace performance has grown into a major aspect of business entities, which is also gaining momentum in recent empirical research [3,38]. Goal ambiguity and measurement shortcomings, on the other hand, are the most significant restrictions to workplace performance [39].…”
Section: Workplace Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Workplace performance has been the core of all organizational activities. Moreover, it is the position of Monyei et al [3] and Yasar et al [38] that workplace performance has grown into a major aspect of business entities, which is also gaining momentum in recent empirical research [3,38]. Goal ambiguity and measurement shortcomings, on the other hand, are the most significant restrictions to workplace performance [39].…”
Section: Workplace Performancementioning
confidence: 99%
“…LePine et al [2] observe that the term pro-social behaviour has only recently emerged to describe employees' willful behaviour within various workplace social environments and systems, and it has since grown into a significant field of research, owing to the growing importance of autonomous and team-based work over strict traditional hierarchies [2]. As a result, understanding pro-social behaviour is becoming increasingly important for the long-term survival and sustainability of social networks as well as workplace employee obligations [3][4][5]. Globally, the phrase pro-social behaviour connotes any positive workforce deeds that support the social and psychological relations of organizational members or the workplace itself.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…To effectively do this, resources are required and human resource is one of the important resources of an organisation. According to Monyei et al (2021), finding a solution in the long-term, that sustains a capable workforce able to provide business sustainability remains a puzzling aspect for most organisations. The insurance sector is not immune to these challenges as succession management and organisational sustainability appear to be issues that have continuously challenged the Nigerian insurance industry.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown, that employees are a strong resource of an organisation, with Talpos et al (2017), observing that an organisation's determination to preserve and advance its' intellectual capital for future growth, will in the competitive space, be the only sustainable differentiation. Succession management studies have mainly focused on other sectors such as transportation, manufacturing and small and medium enterprises (Baker, Lunsford, & Pifer, 2018;Monyei et al, 2021;Onyeukwu & Jekelle, 2019) with little or none existing around the insurance space. Hence, it becomes necessary for an empirical study of this nature to review the relationship between these two important constructs.…”
Section: Introductionmentioning
confidence: 99%
“…In an ideal scenario, healthcare centres, households, and communities would incorporate a highly effective waste management system into every aspect of their endeavours, because it is a prerequisite for environmental sustainability (Monyei et al, 2021). However, the environment is currently experiencing lingering turbulence occasioned by inappropriate management of waste (inclusive of classifying and disposing of waste in sanitary arena), which is adversely impacting on the quality of public health and has further transformed into a major problem being experienced globally (Kumar et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%